Estudo da padronização visando à interoperabilidade: o caso das organizações de saúde na cidade de Marília- São Paulo - Miranda, Nelson Júlio de Oliveira [UNESP] (2015)
The evolution of Information and Communication Technologies (ICT), driven by scientific and technological development, has caused and is still causing paradigm shifts for both, the individual and the organizations, and affect all spheres of social structure. In organizations, ICT were inserted in the automation of management processes, with little or no concern about standards, which only occurred when the need for data and information exchange between intra and inter-organizational systems has emerged. Interoperability between systems is understood as the ability of two or more systems to exchange data and information, and should occur in syntactic and semantic levels. For this to happen, agreements must be signed in order to set a standard in writing and meaning of data and information to be exchanged. It is therefore in this perspective that this research was inserted and brought as guiding questions: What is the understanding that the information technology (IT) professionals, who work in healthcare organizations located in the city of Marilia - São Paulo had about standards interoperability and its applicability in these organizations? In what ways the legal system for health data protection, was perceived by the information technology area within these organizations? In healthcare organizations, professional already work with specific standards (HL7, DICOM, openEHR, CID etc.). In addition to these, are also highlighted the MeSH and DeCS. Furthermore, are also adopted the generic infrastructure and communications standards (Ethernet, TCP / IP, HTML, XML, JSON, etc.). Information reference models such as HL7 RIM and RIM openEHR define which information architecture is the ideal in healthcare area. Terminologies and nomenclatures, represented by SNOMED-CT, ICD, LOINC etc., seek to ensure the understanding of the meaning that which is recorded and transferred by the systems. Added to these standards, are the ethical and legal aspects ...